OP0291 Identification of novel susceptibility loci in a large UK cohort of juvenile idiopathic arthritis (JIA) cases. (15th June 2017) - Smith, SL; Bowes, J; Cobb, J; Hinks, A; Sampath, S; Yarwood, A; Wedderburn, L; Hyrich, K; Thomson, W; ,
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a group of chronic arthropathies of unknown cause affecting children under 16yrs, and is the most common childhood inflammatory rheumatic diagnosis. In recent years great advances in dissecting the genetic basis of JIA have been made. In a landmark study, conducted on the two most common subtypes (oligoarthritis and RF-negative polyarthritis), 17 susceptibility loci were identified at genome-wide significance (p-value <5x10 -08 ) and a further 11 reaching suggestive significance (p-value <1x10 -06 ). These findings were the results of a large international collaboration using the ImmunoChip array, targetting 186 known loci in 12 autoimmune diseases. However, a limitation to the afore-mentioned study was that the analysis is limited to the selected loci; large genome-wide studies are now needed. Objectives: The aim of this work is to identify novel genetic loci associated with disease susceptibility using a large cohort of UK JIA cases Methods: Whole-genome genotyping data was generated using four platforms (Illumina). Following stringent quality control common variants to all four platforms were extracted from the individual datasets before merging together. Imputation was performed using the Haplotype Reference Consortium panel on the Michigan Imputation Server using Minimac3 software. SNPs with imputation accuracy (r 2 >0.5), minor allele frequency >1% and Hardy-Weinberg p-value>1x10 -03 were retained for analysis. Association was conducted using logistic regression; using the top three principal components as covariates. Bioinformatics analysis was performed using in-house Capture Hi-C data, to study long-range interactions, to elucidate the potential function of the associated SNPs Results: Post-QC, 2, 585 cases and 5, 181 controls were available for analysis with ∼7.4 million SNPs. Analysis conducted within oligoarthritis and RF-negative polyarthritis cases, (n=1, 617) confirmed 13 previously identified JIA risk loci and identified more than 20 potentially novel regions above suggestive significance (2.25x10 -05 ). Of these, rs7874896, an intergenic SNP located between TNFSF15 and TNFSF8 on chromosome 9 was one of the most strongly associated (p-value 3.67x10 -07 ). TNFSF15 is particularly interesting as by homology and function, is very similar to TNFα. Furthermore, in Crohns disease, it has been found that TNFSF15 drives expression of pro-inflammatory cytokines (IFNγ) and TNFα from CD4+CD161+ T-cells, yet these cells were found to be resistant to anti-TNF treatment; suggesting that blockade of TNFSF15 may possess therapeutic benefit. Further investigation of SNPs within the TNFSF15/TNFSF8 gene region using Capture Hi-C data yielded potentially interesting interactions both within this region and with nearby genes within T- and B-cell lines Conclusions: This study represents the largest GWAS conducted in JIA to date and our preliminary results have identified novel associations with the most common subtypes of the disease and may have highlighted a potentially novel therapeutic target Acknowledgements: We thank Arthritis Research UK for their support: grants 20380 and 20385. CAPS was funded by Arthritis Research UK: grant 20542 Disclosure of Interest: None declared